UJI AKTIVITAS ANTIOKSIDAN PADA ASTEROIDEA (Linckia laevigata) DARI PERAIRAN TONGKAINA KECAMATAN BUNAKEN KOTA MANADO - Kristoper A Lidongi; Chatrien A.L. Sinjal; Kurniati Kemer; Remmy E.P. Mangindaan; Grevo Soleman Gerung; Sammy Londong (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Indonesia has abundant biological resources that produce many potential bioactive compounds that are useful for pharmaceuticals and other materials, one of which is antioxidants. Antioxidants are substances that can prevent or slow down cell damage caused by free radicals. This study aims to analyze how strong the antioxidant activity is in the body of asteroidea (Linckia laevigata) taken in Tongkaina waters, Bunaken District, Manado City. And this study found that the inhibition value of the ethanolic extract of Linckia laevigata had strong antioxidant activity where the extract increased and the concentration was 10 mg/L with an average value of 67,3 %, a concentration of 15 mg/LÂ  of 67,8 %, a concentration of 20 mg/L of 68,8 % and the highest concentration of 25 mg/L getting an average value of 69 %. The increace in the percentage of inhibition and the ethanolic extract of Linckia laevigata, showed that the concentration of the extract contributed greatly to the ability of the extract to reduce free radicals. In this study, the DPPH test was carried out by observing the decrease in absorbance wavelength of 517 nm using UV-Vis spectrophotometer,where the decrease in absorbance value as a result and a decrease in color intensity. While vitamin C as a comparison has a greater yield and sample extract of Linckia laevigata which proves that the antioxidant content and the sample has a fairly stable result.Keywords: Bioaktif compounds, Linckia laevigata, Antioxidant, Vitamin C